Three-level containment model of hospitalized adolescents with borderline pathology: a holistic therapeutic perspective - Robin, Marion; Bellone, Laura; Belbèze, Jean; Kazemian, Koucha; Radjack, Rahmeth; Corcos, Maurice (Frontiers in Psychiatry, 2023)
Borderline personality disorders account for 50% of adolescent hospitalization cases in psychiatry. The severity and psychopathological complexity of these symptoms indicate the need for inclusive models of understanding. Adopting a holistic approach allows for the consideration of not only the patient's environment, but also their position within that environment and their life history. In this article, a model based on the concept of therapeutic containment at three levels is presented. Global containment refers to the mindset and organization of the institution that provides care, which is itself a part of society at a specific time. Local containment focuses on understanding and therapeutic interventions within the immediate social environment of the individual. Lastly, individual containment encompasses the development of independent processes during the course of care. These three levels are integrated in the hospital treatment of borderline personality disorders, forming a trans-theoretical approach.